The effect of Hijamah on different health parameters - Allafi, Ahmad R; Al-Haifi, Ahmad R (Progress in Nutrition, 2020)
Objectives: To find Hijamah as preferred and accepted therapeutic procedure because of its effectivenessand safety in comparison to manufactured drugs toxicity. Cholesterol, triglycerides, blood sugar and bloodpressure were selected to investigate the effectiveness of Hijamah in the current study. Subject and Method:twenty healthy females were selected as subjects for Hijamah in this study. The selected females were 25-38years old. Their blood samples were collected and a routine biochemical assessment was carried out on collected venous blood samples. This assessment is carried out two times, once before Hijamah at baseline time and then after ten days of Hijamah. Result: The blood assessment results were compared and it is found that blood pressure (systolic and diastolic) was significantly reduced after Hijamah (P